Primary Cutaneous Gamma-Delta T-Cell Lymphoma With Long-Term Indolent Clinical Course Initially Mimicking Lupus Erythematosus Profundus - von Dücker, Laura; Fleischer, Mariella; Stutz, Nathalie; Thieme, Markus; Witte, Mareike; Zillikens, Detlef; Sadik, Christian D.; Terheyden, Patrick (Frontiers in Oncology, 2020)
Primary Cutaneous Gamma-Delta (γδ) T-Cell Lymphoma (CGDTCL) is a rare primary cutaneous lymphoma of aggressive nature. Only a few cases with an initially indolent course over years have been published. CGDTCL can mimic diseases with benign behavior in their clinical and histopathological presentation, such as lupus erythematosus profundus, but also other lymphomas, for example subcutaneous panniculitis-like T-cell lymphoma. In our patient, the results of histopathological, immunofluorescence microscopy, and clinical examinations of early lesions first led to the diagnosis of lupus erythematosus profundus. When disease progressed six years later, a hemophagocytic syndrome and a CGDTCL with an aggressive course was diagnosed. Reevaluating a former biopsy, an early CGDTCL was retrospectively diagnosed. A distinct correlation of clinical, histopathological, immunohistochemical, and molecular-pathological examinations is needed to differentiate between the potentially malignant and benign diseases. Re-biopsies of different skin lesions in uncertain cases are strongly indicated. Besides clinical symptoms such as fever or weight loss, changes in the blood count or a rising LDH can be a hint for a CGDTCL making regular clinical and laboratory monitoring essential. This case demonstrates that an indolent clinical phenotype can precede an aggressive clinical course in CGDTCL.